Association of uric acid and red blood cell distribution width with severe obstructive sleep apnea–hypopnea syndrome in middle-aged males - Tingting Zhou; Hongyan Tao; Hong Wang; Fengxian Wei (PLoS ONE, 2026)
Background Obstructive sleep apnea-hypopnea syndrome (OSAHS) is sleep-related breathing disorder with high prevalence. Polysomnography is the gold diagnosis standard. Routine clinical biomarkers would assist to reflect disease severity. Our study aimed to explore the association between hematological parameters and newly diagnosed severe OSAHS in middle-aged males. Methods This retrospective study enrolled 132 cases (40 ~ 65 years). Patients were divided into non-severe group (n = 69) and severe group (n = 63) based on the apnea-hypopnea index (AHI). Hematological parameters were compared between the two groups. Unitarian and multivariate logistic regression were performed to identify factors independently correlated with severe OSAHS. Receiver operating characteristic (ROC) curve analysis was performed to evaluate discriminative performance. Spearman correlation and multiple linear regression were utilized to investigate correlated factors with sleep hypoxia. Results Significantly higher hemoglobin, hematocrit (HCT), mean corpuscular volume (MCV), red blood cell distribution width-standard deviation (RDW-SD), and uric acid were found in the severe group than the non-severe group (all P < 0.05). Multivariate logistic regression identified uric acid as the only independent correlate of severe OSAHS (OR = 1.01, P = 0.012). The combination of uric acid and RDW-SD yielded an AUC of 0.79 (95% CI: 0.69–0.89), with a sensitivity of 77.4% and specificity of 80.4%. Spearman analysis showed that uric acid correlated significantly with sleep mean SpO 2 (r = –0.26, P = 0.034) and sleep minimum SpO 2 (r = –0.30, P = 0.014), but not with AHI (r = 0.19, P = 0.123). In multiple linear regression adjusted for age and BMI, both uric acid and RDW-SD remained independently associated with sleep mean and minimum SpO 2 (P < 0.001). Conclusions Uric acid and RDW-SD are independently associated with OSAHS severity and sleep hypoxia in middle-aged males. The combination of these two routine clinical markers may offer useful information for risk stratification, while prospective studies is needed for validation.